PENGGALI KUBUR DI TEMPAT PEMAKAMAN UMUM KECAMATAN TAMPAN KOTA PEKANBARU - Sari, Fatma; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Gravediggers at the Tampan District Public Cemetery Pekanbaru City. This research was conducted at the Public Cemetery in Tampan District Pekanbaru City. The purpose of this study was to determine the social capital of gravediggers by using qualitative descriptive research methods and using data collection techniques through direct observation, interviews, and documentation. Retrieval of informants using purposive sampling technique, provided that informants are based on predetermined characteristics. The number of informants in this study were four gravediggers with the status of casual daily laborers at the Tampan District Public Cemetery. The results obtained are that the gravedigger social capital includes three elements, namely social networks, beliefs and norms. These three elements are interrelated by strengthening each other. With the existence of social capital, gravediggers can maintain harmony with one another, cooperate well and help each other in the economic and work fields. Keywords: Gravedinggers, Sosial capital